Penggunaan Metode McCall dalam Pengukuran Sistem Informasi Pelaporan Perkara Penahanan Berbasis Web Pada Pengadilan Negeri Sumber Cirebon - Wahyudin Tajmi; Tuti Hartati (Jurnal Accounting Information System (AIMS), 2022)
The Sumber District Court in managing the detention case reporting, the applicant still uses physical files which must be sent directly to the Sumber District Court. This process often results in unintentional errors in the reporting system, so that the applicant needs one week to receive the case determination report from the Sumber District Court. Seeing the problems above, the solution to this problem is to create a web-based case reporting application. The purpose of this study is to build a web-based case reporting application that can minimize the occurrence of missing, damaged, repeated reports and revised reports for the applicant and after that the case reporting system is tested for feasibility. Making applications using the Waterfall Method, PHP MySQL language, for testing the feasibility of the application, namely the McCall method. The results of the research are in the form of a reporting system that can be accessed on the http://pintas.pn-source.go.id page. The results of the feasibility test using the McCall method refer to the quality of the software which has five factors of correctness, usability, integrity, reliability, efficiency. Testing the application to get the results of 55.68% is between 41% - 60% is included in the fairly good category.